Seasonal Influenza Vaccine Effectiveness in Preventing Laboratory-Confirmed Influenza in Primary Care in Israel, 2016–2017 Season: Insights Into Novel Age-Specific Analysis. (14th November 2017) - Stein, Yaniv; Mandelboim, Michal; Sefty, Hanna; Pando, Rakefet; Mendelson, Ella; Shohat, Tamy; Glatman-Freedman, Aharona
Abstract : Vaccine effectiveness (VE) against influenza A(H3N2) was evaluated for the 2016–2017 season in Israel. VE varied among different age groups. The highest VE estimate was found in those aged 5–17 and 45–64 years. A novel age-specific analysis was developed. Abstract: Background: The 2016–2017 influenza season in Israel was dominated by the circulation of influenza A(H3N2). Influenza vaccine is recommended for the entire population in Israel aged >6 months. The inactivated influenza vaccine was chosen for use this season. Methods: We estimated the 2016–2017 end-of-season influenza vaccine effectiveness (VE) in preventing influenza-like illness due to influenza A(H3N2), using the test-negative design. Age-specific VE was estimated using a moving age window and weekly analysis. Results: During the 2016–2017 season, 1267 samples were collected; 467 (36.9%) were positive for influenza, with 97.9% A(H3N2), 0.2% A(H1N1)pdm09, and 1.9% B. A total of 1088 individuals were found eligible to be included in VE assessment. All vaccinated individuals included in the VE assessment received the inactivated influenza vaccine. Adjusted VE against influenza A(H3N2) was 29.0% (95% confidence interval [CI], 0.3%–49.5%). Age group–specific adjusted VE was 69.2% (95% CI, 19.4%–88.3%) for children aged 5–17 years and 58.8% (95% CI, .8%–82.9%) for adults aged 45–64 years. Other age groups demonstrated lower VE estimates that were not statistically significant. Adjusted VE estimates using a moving window of 15 years and weekly VE analyses provided a more defined understanding of age-specific VE during the 2016–2017 season. Conclusions: Estimating VE using a moving age window as well as weekly VE analysis may provide more detailed information regarding the relationship between VE and age.